Does Size Affect Loan Portfolio Structure and Performance of Domestic-Owned Banks In Indonesia? - Atahau, T.; Cronje, Tom (Virtus Interpress, 2015)
Domestic-owned banks (DBs) represent almost 40% of the overall number of banks in Indonesia. The objective of this study is to determine whether small and large Indonesian DBs differ in terms of their loan portfolio structures and performance. No previous studies addressed this issue. The study is based on 9 year loan portfolio structure and performance data of 69 large and 346 small Indonesian DBs. Descriptive statistics, univariate statistics and panel data regression are applied. The findings from univariate statistics show that the loan portfolio structures and returns of small and large DBs differ significantly. However, panel data regression shows that only the loan portfolio return-risk relationship of small and large DBs differs significantly.